Clinical Practice Guidance for Management of Anti HBc Positive Patients (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Hepatitis B core antibody (Anti HBc) is currently considered the most sensitive serological marker for a patient’s history of hepatitis B virus (HBV) infection given its long-term persistence in the bloodstream. The serological pattern of isolated Anti HBc (IAHBc) has been of clinical interest over the past several years.,Thegrowing data of IAHBcsuggestingit as a marker for occult HBV infection (OBI). Occult HBV infection defined as HBV DNA detection in serum or the liver by sensitive diagnostic tests in HBsAg negative individuals with or without serologic markers of previous viral exposure. OBI is especially concerned in blood transfusion (BT), organ donation and reactivation of HBV infection following immunosuppressive therapy. HBV reactivation depends on viral and host factors. The important clinical implications of IAHBcis in the setting of co-infection with hepatitis C virus (HCV), reactivation risk of HBV during directly acting anti viral (DAA) therapy in HCV infection which may lead to progression of liver disease and hepatocellular carcinoma (HCC). Antiviral prophylaxis has been recommended in moderate to high risk of reactivation prior to immunosuppressive and biologics. The main goal of therapy is to improve survival and quality of life by preventing disease progression and to prevent consequent development of HCC. It is proposed to perform Anti-HBc test as a screening test prior to blood transfusion, HBVvaccination, DAA and immunosuppressive therapy in addition to HBsAg screening test.J Bangladesh Coll Phys Surg 2019; 37(4): 196-201